Мониторинг состояния экземпляров сервисов и метод обеспечения требуемого уровня надежности - Копытова, Е. А.; Фауаз Саид Халава (Проблеми телекомунікацій, 2012)
The method of ensuring reliability of service in multiservice networks based on service-oriented architecture was proposed. This method allows to increase the efficiency of network management through the implementation of choice based on the service instance information on copies of obtained by the monitoring system.
Keywords: система управления; сервис-ориентированная архитектура; экземпляр сервиса